2001
DOI: 10.1016/s0005-2736(01)00303-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antimicrobial peptide interactions with hybrid bilayer membrane systems using surface plasmon resonance

Abstract: The lipid binding behaviour of the antimicrobial peptides magainin 1, melittin and the C-terminally truncated analogue of melittin (21Q) was studied with a hybrid bilayer membrane system using surface plasmon resonance. In particular, the hydrophobic association chip was used which is composed of long chain alkanethiol molecules upon which liposomes adsorb spontaneously to create a hybrid bilayer membrane surface. Multiple sets of sensorgrams with different peptide concentrations were generated. Linearisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
3
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(203 citation statements)
references
References 45 publications
13
185
3
2
Order By: Relevance
“…The present results therefore reveal that the C-terminal charges of melittin reduce the affinity of the peptide for neutral membranes. These conclusions are in contradiction with those inferred from the SPR binding studies concluding that truncated amidated melittin-21Q exhibits, relative to melittin, a lower or a similar affinity for DMPC membranes 45,46 . These SPR experiments were conducted on supported bilayers and the nature …”
Section: Acs Paragon Plus Environmentcontrasting
confidence: 92%
See 1 more Smart Citation
“…The present results therefore reveal that the C-terminal charges of melittin reduce the affinity of the peptide for neutral membranes. These conclusions are in contradiction with those inferred from the SPR binding studies concluding that truncated amidated melittin-21Q exhibits, relative to melittin, a lower or a similar affinity for DMPC membranes 45,46 . These SPR experiments were conducted on supported bilayers and the nature …”
Section: Acs Paragon Plus Environmentcontrasting
confidence: 92%
“…For instance, the properties of melittin-21Q, a truncated analogue of melittin in which residues 21 to 25 (K 21 -R 22 -K 23 -R 24 -Q 25 ) were omitted, were investigated. Its binding to zwitterionic 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) bilayers as well as to anionic 1,2-dimyristoyl-sn-glycero-3-phosphoglycerol (DMPG) bilayers was measured by Surface Plasmon Resonance (SPR) [45][46] . Melittin-21Q exhibited a reduced or similar binding to DMPC and to DMPG bilayers compared to native melittin, suggesting a favorable or a limited contribution of the cationic C-terminal portion to membrane affinity.…”
Section: Introductionmentioning
confidence: 99%
“…We have already established an evaluation method of the interactions of various peptides to lipid membranes using SPR, [9][10][11][12][13][14][15] and demonstrated that the kinetic rate constants and the affinity of membrane interactions can be readily determined by this technique, which in turn provides important insights into the mechanism of peptide-membrane interactions. In the present study, we extended our studies into the membrane binding properties of the AT peptide.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding differential rate equations for this reaction model are represented by [18][19][20][21][22][23] …”
Section: Discussionmentioning
confidence: 99%